English for computer science = Tiếng Anh chuyên ngành vi tính (Thống kê, 1999)
What is the computer; History of computer; Characteristics; Comouter capabilities and limitations; Maimframes; Minicomputers; Microcomputer; The central processing unit; The control unit and the arithmeticlogical unit.